A sabiendas de lo incierto… - Cantero, Pedro A. (Revista de Antropología Social, 2008)
It could be said that both anthropology and literature take the human being as an object of study, but something radically differentiates them. Literature focuses on narration, reflection more than reasoning; anthropology, by contrast, bases itself in discourses. As an anthropologist, I feel that “literal” exactitude is more and more urgent. Nevertheless, I know that in doing so I tend to obscure the dark side of the facts; I distort life itself, ultimately desiccating it. I situate my argument within this paradox.
Keywords: Truth; Fraud; Writing; Science; Ethnography; Evidence; Imaginary; Reconstruction; Fiction